2022
DOI: 10.1038/s41598-022-22111-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression of Ce and Pr with millisecond time-resolved X-ray diffraction

Abstract: Both cerium (Ce) and praseodymium (Pr) undergo a volume collapse transition under compression that originate from similar electronic mechanisms. Yet the outcome could not be more different. In the case of Ce with one affected 4f electron the volume collapse leaves the crystal symmetry intact, whereas for Pr with two 4f electrons the crystal symmetry changes from a distorted face centered cubic structure to a lower symmetry orthorhombic structure. In this paper, we present a study of the effect of strain/compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…pubs.aip.org/aip/rsi dDACs have been employed to study the compression rate dependence of phase transitions in metals such as bismuth, cerium, praseodymium, 13,14 hydrogen, 15 and KCl. 16 In these studies, the compression rate is observed to behave as a "third dimension" within a pressure-temperature phase diagram.…”
Section: Articlementioning
confidence: 99%
“…pubs.aip.org/aip/rsi dDACs have been employed to study the compression rate dependence of phase transitions in metals such as bismuth, cerium, praseodymium, 13,14 hydrogen, 15 and KCl. 16 In these studies, the compression rate is observed to behave as a "third dimension" within a pressure-temperature phase diagram.…”
Section: Articlementioning
confidence: 99%
“…Investigation of material behaviour during dDAC compression requires appropriate time-resolved diagnostics which are compatible with the compression timescale. The development of high-frame-rate photon-counting X-ray detectors such as the LAMBDA (Pennicard et al, 2013) and the EIGER has permitted time-resolved X-ray diffraction (XRD) studies of dDAC-compressed samples to be performed at synchrotron radiation sources (Marquardt et al, 2018;Me ´ndez et al, 2021Me ´ndez et al, , 2022Husband, O'Bannon et al, 2021;Schoelmerich et al, 2022;O'Bannon et al, 2022), where high-Z sensors enable efficient detection of high-energy photons which are essential to penetrate the diamond anvils (!10 keV) and provide sufficient access to reciprocal space for XRD experiments. However, minimum exposure times of $ 500 ms have in practice limited kinetic studies to compression rates of $ 1 TPa s À1 ( _ " " ' 10 À1 s À1 ) -two orders of magnitude slower than achievable with the dDAC -in order for phase transition boundaries to be determined to within $ 0.25 GPa (Husband, O'Bannon et al, 2021;O'Bannon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%